Histopathologically atypical astroblastoma with MN1-CXXC5 fusion transcript diagnosed by methylation classifier - Wallace, Gerald C; Macaulay, Robert JB; Etame, Arnold B; Aldape, Kenneth; Pina, Yolanda (Archives of Community Medicine and Public Health, 2022)
Adult astroblastoma is an exceedingly rare primary brain tumor. Previous reports have suggested various radiographic and histological features typical for these tumors, but the diagnosis can be challenging. We present a unique case of astroblastoma diagnosed after 13 years of treatment as a CNS embryonal neoplasm. Histologically, this tumor lacked previously identified astroblastic features such as pseudorosettes, trabeculated patterns, and hyalinized vessels. The tumor was synaptophysin positive which further confounded the diagnosis in this case. Methylation classification was performed with a high confidence match to a high-grade neuroepithelial neoplasm with a CXXC5-MN1 fusion. Molecular characterization confirmed a CXX5-MN1 fusion transcript which has been seen in at least one other instance. Though known to be involved in tumorigenesis, the roles of CXXC5 and MN1, in this case, remain unclear. We discuss the unusual histopathological features of this tumor and the value of recent updates to the WHO molecular diagnosis scheme for central nervous system tumors. We also briefly review the literature related to astroblastoma. The current case highlights our evolving recognition of atypical histological patterns for astroblastoma and the importance of new molecular profiles which can aid in the diagnosis.